Lessons Learned From a Case of Gastric Cancer After Liver Transplantation for Hepatocellular Carcinoma: A Case Report and Literatures Review. Issue 7 (February 2016) - Yang, Kun; Zhu, Hong; Chen, Chong-Cheng; Wen, Tian-Fu; Zhang, Wei-Han; Liu, Kai; Chen, Xin-Zu; Guo, Dong-Jiao; Zhou, Zong-Guang; Hu, Jian-Kun
Abstract : Abstract: Nowadays, de novo malignancies have become an important cause of death after transplantation. According to the accumulation of cases with liver transplantation, the incidence of de novo gastric cancer is anticipated to increase among liver transplant recipients in the near future, especially in some East Asian countries where both liver diseases requiring liver transplantation and gastric cancer are major burdens. Unfortunately, there is limited information regarding the relationship between de novo gastric cancer and liver transplantation. Herein, we report a case of stage IIIc gastric cancer after liver transplantation for hepatocellular carcinoma, who was successfully treated by radical distal gastrectomy with D2 lymphadenectomy but died 15 months later due to tumor progression. Furthermore, we extract some lessons to learn from the case and review the literatures. The incidence of de novo gastric cancer following liver transplantations is increasing and higher than the general population. Doctors should be vigilant in early detection and control the risk factors causing de novo gastric cancer after liver transplantation. Curative gastrectomy with D2 lymphadenectomy is still the mainstay of treatment for such patients. Preoperative assessments, strict postoperative monitoring, and managements are mandatory. Limited chemotherapy could be given to the patients with high risk of recurrence. Close surveillance, early detection, and treatment of posttransplant cancers are extremely important and essential to improve the survival.